Hh-Gli signaling pathway functions and its therapeutic potential in cancer - Levanat, Sonja; Čretnik, Maja; Musani, Vesna (2008)
Summary: Hh-Gli signaling pathway is one of the major and highly conserved pathways regulating embryogenesis and organ development. Its aberrant functioning is associated with malformations and cancer. Major proteins involved in the pathway are Hh, Ptch, Smo, and Gli1. Recent discoveries showed that the pathway is involved in many common and lethal tumors, such as breast, lung, prostate and digestive tract cancer. In these cases, tumor growth appears to require abnormal Hh stimulation from the surrounding cells, which causes a strong intracellular response of the pathway. Extensive involvement of the Hh-Gli pathway in tumor development has promoted it into an important target for cancer therapy, by discovery of a small molecule, cyclopamine, which was shown to block Smo. Successful tumor growth inhibition was accomplished both in cell cultures and on animal models. Current research includes analogous molecules, and alternative strategies of intervention on the other elements of the Hh-Gli pathway
Bibliografija: 38 jed.
Sažetak
Keywords: Signalni put Hh-Gli -- Embrionalni razvoj -- Prirođene anomalije -- Gorlin-Goltzov sindrom -- Tumori -- Ciklopamin -- Protutumorski učinak